PERILAKU PROSOSIAL PESERTA DIDIK SEKOLAH DASAR BERDASARKAN PERBEDAAN JENIS KELAMIN - Amini, Yustiana; Saripah, Ipah (Mimbar Sekolah Dasar, 2016)
The aim of this research is to provide an overview of empirical research to the student prosocial behavior in elementary school. The approach used to examine the student prosocial behavior is a quantitative approach with descriptive methods. The population is 84 high-grade student's SD Miftahul Iman Year 2015/2016. Results show that the overall level of prosocial behavior is the adequate category with average value of 1.89, which indicates that students are already quite capable of showing their prosocial behavior but still require the guidance of a counselor or teacher. Based on sex, there is difference but not significant in the average value of prosocial behavior among girl and boy students.Keywords: prosocial behavior, elementary student, sex difference.